Immunosuppressive nano-therapeutic micelles downregulate endothelial cell inflammation and immunogenicity. Issue 54 (13th June 2015) - Nadig, Satish N.; Dixit, Suraj K.; Levey, Natalie; Esckilsen, Scott; Miller, Kayla; Dennis, William; Atkinson, Carl; Broome, Ann-Marie
<x xml:space="preserve">Abstract</x> Targeted micelles containing rapamycin (TRaM) suppressed the immune response of IL-8 in oxidatively stressed human umbilical vein endothelial cells in vitro (a) and accumulated in aorta grafts for transplantation after 6 hours in cold perfusion solution (b).